GAMBARAN PERILAKU PENCARIAN PELAYANAN PENGOBATAN PADA MASYARAKAT DUSUN VI DESA PATUMBAK KAMPUNG KABUPATEN DELI SERDANG TAHUN 2013 - ronauli saragih; Lita Sri Andayani; Tukiman . (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
ABSTRACT   The searching process for medical care or treatment is a process that can not be separated from human’s life because every people in their lives is never detached from disease problem. Four medication pattern that developed in Desa Patumbak Kampung is by self medication healing to the disease suffered, by using the traditional medication, by using modern medication, and the fusion between traditional and modern medication. The purpose of this research is to describe behaviour of medication in  Dusun VI Desa Patumbak Kampung. This research is a descriptive research with quantitative methodology approach. The result is analyzed descriptively and quantitatively, and presented in percentage amount. The respondence that have been interviewed are 81 respondences. Data collected by questionnaire module, as a guide of inquiry during the interview. The results of this research shows, most of the respondence by the age 18-40 years old, is about 53,1%. The majority of unemployed respondence is about 61,7%. Respondence’s education is include in the mediocre level is 71,6%. The respondence’s average earning that > Rp 1.201.000,- is about 71,6%. Public Health officer is include in the low category as much as 72,8%. Famili support is included in the mediocre category by 56,8%. Print/electronic media is included in the high category by 37%. The knowledge level of the repondence is in mediocre level, at 60 respondences(74,1%). The respondence’s behavior  is in the mediocre level, as much as 51 respondences (63%). And for the respondence’s action is in the low level, as much as 44 respondences (54,3%). Based on the research, it is recommended for Patumbak Public Health Service ( Puskesmas Patumbak) to be more sensitive and serious in order to minimalize the obstacle such as the officer’s behavior that still not optimal( less action) in giving the medication service or socializing the health information.